Switching Costs in Frequently Repeated Games - Barton L. Lipman; Ruqu Wang (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1997)
We show that the standard results for finitely repeated games do not survive the combination of two simple variations on the usual model. In particular, we add a small cost of changing actions and consider the effect of increasing the frequency of repetitions within a fixed period of time. We show that this can yield multiple subgame perfect equilibria in games like the Prisoners' Dilemma which normally have a unique equilibrium. Also, it can yield uniqueness in games which normally have multiple equilibria. For example, in a two by two coordination game, if the Pareto dominant and risk dominant outcomes coincide, the unique subgame perfect equilibrium for small switching costs and frequent repetition is to repeat this outcome every period. Also, in a generic Battle of the Sexes game, there is a unique subgame perfect equilibrium for small switching costs.
Keywords: 330